PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DAN PENGEMBANGAN USAHA KECIL MENENGAH: KAJIAN PADA INDUSTRI TENUN GOYOR DI KABUPATEN SUKOHARJO - Aris Eddy Sarwono, Doddy Setiawan, Y. Anni Aryani, Isna Putri Rahmawati & (Universitas Slamet Riyadi, 2016)
Small and Medium Enterprises (SMEs) in Indonesia has a role innational economic development. The main problems of SMEs in addition tothe issue of capital in the development of SMEs is a matter of humanresources (HR). SMEs goyor weaving is one of the SMEs which have hadproblems regarding human resources is primarily on the skills are stilllimited. To overcome these problems, the universities has a role inaddressing the issue.Keywords: SMEs, human resources, weaving goyor, economics